2010
DOI: 10.1111/j.1468-3148.2008.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Attribution Model of Stigma towards Children with Autism in Hong Kong

Abstract: Background Accounting for the effects of knowledge of and experience with autism, the relationships of cognitive attribution (perceived controllability), emotions (anger and sympathy), as well as helping and punitive behavioural intentions towards children with autism were examined. Based on the attribution model, mediating effects of anger and sympathy on cognitive attributions and behavioural intentions were tested. Materials and Methods 123 frontline staff in educational settings completed a modified versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 58 publications
4
47
0
Order By: Relevance
“…Consistent with some prior research (Ling et al 2010;Mahoney 2008, but inconsistent with Butler andGillis 2011), heightened autism knowledge was associated with lower stigma in the US. However, no associations between knowledge and stigma were observed in Lebanon.…”
Section: Predictors Of Baseline Knowledge and Stigma In The Us And Lesupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with some prior research (Ling et al 2010;Mahoney 2008, but inconsistent with Butler andGillis 2011), heightened autism knowledge was associated with lower stigma in the US. However, no associations between knowledge and stigma were observed in Lebanon.…”
Section: Predictors Of Baseline Knowledge and Stigma In The Us And Lesupporting
confidence: 88%
“…Prior studies have found that greater knowledge about ASD is associated with lower stigma (Ling et al 2010;Mahoney 2008; but see Butler and Gillis 2011 for evidence that ASD knowledge is not always associated with stigma). Increased knowledge may be related to lower endorsements of discriminatory attitudes toward a range of diagnostic categories (e.g., Corrigan and Penn 1999;Holmes et al 1999).…”
Section: Stigma Towards People With Asdmentioning
confidence: 96%
“…Although parents of children with ASD did not differ among themselves in parenting stress and psychological well-being outcomes, the effects of some factors on parental well-being outcomes may warrant further investigation. For instance, previous research highlighted that parents' acceptance of child's social and communicative challenges played a role in the impact of parenting stress on psychological well-being outcomes (Lee 2009;Ling et al 2010;Mori et al 2009;Rao and Beidel 2009;Szatmari et al 1995). In addition, factors such as child's daily and ASD-related behaviors (e.g., Lecavalier et al 2006;Huang et al 2014), the level of adaptive functioning of the child (e.g., Abbeduto et al 2004;Hall and Graff 2011;Konstantareas and Papageorgiou 2006), and child's learning abilities and schooling arrangements (e.g., Lee et al 2008;Nevo and Bin Khader 1995) can moderate the intensity of parenting stress felt by parents.…”
Section: Parental Psychological Well-being Outcomesmentioning
confidence: 99%
“…School-age children with ASD are at risk of being stigmatized [63] and being victims of bullying [64] for multiple reasons. They have different developmental trajectories that may put them at greater risk of victimization than their neurotypically developing peers, especially when they have challenges in social skills and communication [64].…”
Section: Introductionmentioning
confidence: 99%